2007
DOI: 10.22605/rrh674
|View full text |Cite
|
Sign up to set email alerts
|

Regular doctor, changing doctor, no doctor: does it make a difference to rural residents?

Abstract: Introduction:In Canada, a larger proportion of rural residents than urban residents do not have a regular physician. In addition to lacking physicians, many rural communities also have a high rate of physician turnover. In order to discover the effect of this we compared health status, lifestyles, preventative care, and perceptions of the health system among rural residents with a regular doctor, those who did not have a regular doctor, and those whose regular doctor changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The review also revealed that a vast majority of the studies have a singular focus on educational interventions situated to influence physician disposition in rural or remote areas, with less consideration for underserved communities in urban areas. Future program evaluations should consider designing curricula and medical education initiatives that expose learners to working in underserved urban communities as populations with certain ethnic, cultural and/or socioeconomic backgrounds residing in urban locations experience challenges with accessing primary care [12][13][14][15][16][17][18]20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review also revealed that a vast majority of the studies have a singular focus on educational interventions situated to influence physician disposition in rural or remote areas, with less consideration for underserved communities in urban areas. Future program evaluations should consider designing curricula and medical education initiatives that expose learners to working in underserved urban communities as populations with certain ethnic, cultural and/or socioeconomic backgrounds residing in urban locations experience challenges with accessing primary care [12][13][14][15][16][17][18]20].…”
Section: Discussionmentioning
confidence: 99%
“…These disparities are even more pronounced amongst vulnerable and minority populations, including Indigenous and Francophone populations [10,11]. Challenges of accessing primary care are also experienced in urban areas by individuals who are unhoused [12], recent immigrants [13][14][15] from certain ethnic or racial backgrounds [14,16,17], with low socioeconomic status [13][14][15]18], individuals who are uninsured [19] and/or without full-time employment [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals living with chronic diseases in Newfoundland and Labrador access health care services primarily through family physicians (Government of Newfoundland and Labrador, 2002). However, high rates of family physician turnover have created a barrier to access and lack of continuity of care for many individuals in the province, particularly in rural areas (Mathews, Edwards, & Rourke, 2008;Mathews & Park, 2007). In response to the prevalence and burden of chronic diseases, the Government of Newfoundland and Labrador (2011) published a policy framework aimed at preventing and managing chronic diseases in the province.…”
Section: Background and Purposementioning
confidence: 99%
“…Approximately 20% of the Canadian population resides in rural areas, but only 9.3% of physicians work rurally [ 9 ]. According to the Chauhan et al [ 10 ] study, one in seven rural physicians plans to leave practice in rural areas within the next two years.…”
Section: Introductionmentioning
confidence: 99%